STUDENTS’ LEARNING INTEREST IN ISLAMIC AND CHARACTER EDUCATION THROUGH THE CONTEXTUAL TEACHING AND LEARNING MODEL - Eva Amelia; Jamal Fakhri; Beti Susilawati (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
This study aims to examine the effectiveness of the Contextual Teaching and Learning (CTL) model in enhancing students’ learning interest in Islamic Religious Education (IRE) at SMP Negeri 11 Bandar Lampung. The background of this research lies in the low level of students’ learning interest, as indicated by their limited active participation and lack of attention to the material, which are attributed to the dominance of lecture-based teaching methods, limited learning media, and minimal variation in assessment techniques. The research employed a Posttest-Only Control Group design with a Simple Random Sampling technique. The sample consisted of two classes: an experimental class that implemented the CTL model and a control class that utilized conventional teaching methods. The research instrument was a learning interest questionnaire comprising 15 statement items, of which 13 were deemed valid, with a high reliability coefficient (α = 0.87). The data were analyzed using normality tests, homogeneity tests, and a t-test. The findings revealed a significant difference between the experimental and control classes. The implementation of the CTL model proved to be effective in enhancing students’ learning interest, as evidenced by increased participation, attentiveness, and active engagement throughout the learning process. The novelty of this study lies in the application of CTL within Islamic Religious Education (IRE) at the junior high school level, an area that has been underexplored, thereby extending the scope of CTL implementation, which has predominantly been applied to science-related subjects. The practical implication of this research is to provide guidance for teachers in designing more varied, interactive, and contextually relevant learning experiences that connect with students’ real-life situations. Consequently, the results of this study contribute to the advancement of educational science and can serve as a foundation for formulating school policies aimed at improving the quality of PAI instruction. ABSTRAK Penelitian ini bertujuan untuk menguji efektivitas model pembelajaran Contextual Teaching and Learning (CTL) dalam meningkatkan minat belajar Pendidikan Agama Islam (PAI) pada siswa SMP Negeri 11 Bandar Lampung. Latar belakang penelitian ini adalah rendahnya minat belajar siswa yang ditunjukkan melalui kurangnya keterlibatan aktif dan perhatian terhadap materi, yang disebabkan oleh dominasi metode ceramah, keterbatasan media, dan variasi evaluasi yang minim. Penelitian menggunakan desain Posttest-Only Control Group dengan teknik Simple Random Sampling. Sampel terdiri dari dua kelas, yaitu kelas eksperimen yang menerapkan CTL dan kelas kontrol yang menggunakan metode konvensional. Instrumen penelitian berupa angket minat belajar dengan 15 butir pernyataan, di mana 13 dinyatakan valid dan reliabilitasnya tinggi (α = 0,87). Data dianalisis menggunakan uji normalitas, homogenitas, dan  uji-t. Hasil penelitian menunjukkan adanya perbedaan signifikan antara kelas eksperimen dan kelas kontrol. Penerapan CTL terbukti efektif meningkatkan minat belajar siswa, ditandai dengan meningkatnya partisipasi, perhatian, dan keterlibatan aktif selama pembelajaran. Kebaruan (novelty) penelitian ini terletak pada penerapan CTL dalam pembelajaran PAI di tingkat SMP, yang sebelumnya belum banyak diteliti, sehingga memperluas konteks penerapan CTL yang selama ini lebih dominan pada mata pelajaran eksakta. Implikasi penelitian ini adalah memberikan panduan bagi guru dalam merancang pembelajaran yang lebih variatif, interaktif, dan relevan dengan kehidupan nyata siswa. Dengan demikian, hasil penelitian ini berkontribusi dalam pengembangan ilmu pendidikan dan dapat dijadikan dasar perumusan kebijakan sekolah untuk meningkatkan kualitas pembelajaran PAI.